A picture of Carla B. Landsman, State University... - University at Albany (University Photograph Collection, 1977)
A picture of Carla B. Landsman, State University of New York at Albany, Class of 1979 and member of the State University of New York at Albany gymnastics team. She is performing an exercise on the balance beam during the 1977-1978 season.